Assessing the Prevalence and Risk Factors of Malaria Among School Pupils in Muhammad Nya Nursery and Primary School, Jalingo, Taraba State, Nigeria - Allahnanan Emmanuel; Chibuzor Obiorah Sylvester; Grace Fred Wayas; Peace Christopher Njideka; Rasheedat Saidu Ajiya (Darul Yasin Al Sys, 2025)
Malaria remains a significant public health challenge in sub-Saharan Africa, particularly among school-aged children who face increased exposure to mosquito vectors. This cross-sectional study assessed the prevalence of malaria and associated risk factors among 100 pupils (aged 6–12 years) at Muhammad Nya Nursery and Primary School in a malaria-endemic region. Using rapid diagnostic tests (RDTs) and structured questionnaires, we found an overall malaria prevalence of 82.0%, with no statistically significant differences by age group (χ² = 0.581, p > 0.05) or sex (male: 82.8%; female: 81.0%; χ² = 0.054, p > 0.05). However, environmental and behavioral risk factors showed strong associations: stagnant water near households (93.4% vs. 45.8%; χ² = 27.985, p = 0.000), non-use of mosquito nets (96.4% vs. 64.4%; χ² = 17.084, p = 0.000), absence of indoor insecticide spraying (92.3% vs. 62.9%; χ² = 13.368, p = 0.000), and infrequent cleaning of mosquito breeding sites (94.6% vs. 65.2%; χ² = 8.474, p = 0.014) were all linked to higher infection rates. These findings underscore the critical role of environmental management and preventive measures in malaria control. While consistent with broader literature on risk factors, the study highlights the need for context-specific interventions, improved community education, and stronger policy implementation to reduce malaria burden among schoolchildren. Limitations include small sample sizes in some age groups and reliance on self-reported data, suggesting avenues for future research with larger samples and molecular diagnostics.